Analisis Efektivitas Bansos dalam Menunjang Kebutuhan Hidup Warga Desa Marindal 1 - Sinaga, Eko Pranata; Br. Marbun, Tasya; Purba, Widya Helen Anjalina; Harahap, Putra Pratama; Ivanna, Julia (Majalah Ilmiah METHODA, 2024)
This article was created to determine the effectiveness of providing social assistance on the living needs of the people in Marindal I. This research uses a qualitative descriptive method, which means data collection techniques in the form of interviews and literature studies as support for writing this article at the research site in Marindal 1 village. Findings What can be found in the field is that the social assistance distributed has a very effective role in supporting people's living needs, especially in the sector of children's education costs which are greatly helped through social assistance in the form of cash.